CHICKEN EGGS MARKETING CHANNELS IN KALEDUPA ISLAND, WAKATOBI REGENCY - ARSAD SANI, LA ODE; AKA, RAHIM; MUH. MUNADI, LAODE; ., ANSARUDDIN (Majalah Ilmiah Peternakan; Vol 24 No 3 (2021): Vol. 24 No. 3 (2021)DO - 10.24843/MIP.2021.v24.i03.p02, 2021)
This study aims to determine the marketing channels of broiler eggs on Kaledupa Island, Wakatobi Regency by analyzing marketing channels and marketing margins of broiler eggs with the research sample being all traders of purebred chicken eggs in the Sampuawatu market and the Buranga market, Kaledupa district as many as 13 traders analyzed descriptively. The results of the analysis show that there are 755 racks of purebred eggs every month and 345 racks from outside the market, which are imported every 1.100 shelves on the Bau-bau-Kaledupa route, 720 shelves, and the Wanci-Kaledupa route, with 380 shelves. The marketing channels for broiler chicken eggs on Kale- dupa Island are (1) Bau-bau traders - final consumers, (2) Bau-bau traders - collector traders - final consumers, (3) Bau-bau traders - retail traders - final consumers, (4) Bau-bau traders - collector traders - retailers-end consumers, (5) Bau-bau traders-Wanci traders-end consumers, (6) Bau-bau traders-Wanci traders-collectors-end consumers, (7) Bau-bau traders-Wanci traders-retailers-end consumers, and (8) Bau-bau traders Wanci traders-collector tra- ders-retailers-end consumers. The efficient marketing margin of broiler eggs in Kaledupa District is IDR 2.250/rack and the less efficient is IDR 9.250/rack.